DFT and DFT+U Insights into the Physical Properties of UO2 - Islam, M. (Journal of Scientific Research, 2023)
This study reports the structural, electronic, magnetic, elastic, thermal, and optical properties of UO2 solid crystalline material by applying DFT and DFT+U approximation methods. The direct band gap Mott-Insulating electronic properties are found successfully by using both the LDA+U and GGA+U functionals, and the energy band gap values are obtained in the range from 1.725 to 2.860 eV. The XRD and Neutron diffraction peaks confirmed the fcc-structured fluorite type UO2. UO2 is found mechanically stable and ductile from elastic constants calculations. The lattice thermal conductivity is 8.8 Wm-1 K-1 at 323 K, which is very close to the reported theoretical and experimental results. The frequency-dependent optical parameters are calculated from complex dielectric functions, which indicate that UO2 is simultaneously an efficient absorber and reflector for ultraviolet radiation in particular energy regions. Although UO2 is a potential fuel material and cannot be used for conventional optical devices, the anisotropic optical properties, higher dielectric constant, and semiconducting electronic property indicate that the radioactive UO2 exhibits interesting optoelectronic behaviors also.